THE EFFECT OF TRANSFER PRICING , SALES GROWTH AND PROFITABILITY ON TAX AVOIDANCE WITH FIRM SIZE AS A MODERATING VARIABLE IN ENERGY SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Melita Manurung; Rina Bukit; Irman Syarif (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the effect of transfer pricing, sales growth and profitability on tax avoidance with the company size pandemic as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange in 2021-2023. This type of research is quantitative which uses secondary data with testing tools in the form of EVIEWS 12, and the sample used was 38 energy sector companies with purposive sampling technique as the sample selection technique. The results of hypothesis testing show that Transfer pricing and sales growth have a positive and significant effect on tax avoidance. Profitability has a negative and significant effect on tax avoidance. Company size significantly moderates the effect of transfer pricing and sales growth on tax avoidance. Company size does not significantly moderate the effect of profitability on tax avoidance.